If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1(2x + 7) = -9x + -2(4x + 3) Reorder the terms: 8x + -1(7 + 2x) = -9x + -2(4x + 3) 8x + (7 * -1 + 2x * -1) = -9x + -2(4x + 3) 8x + (-7 + -2x) = -9x + -2(4x + 3) Reorder the terms: -7 + 8x + -2x = -9x + -2(4x + 3) Combine like terms: 8x + -2x = 6x -7 + 6x = -9x + -2(4x + 3) Reorder the terms: -7 + 6x = -9x + -2(3 + 4x) -7 + 6x = -9x + (3 * -2 + 4x * -2) -7 + 6x = -9x + (-6 + -8x) Reorder the terms: -7 + 6x = -6 + -9x + -8x Combine like terms: -9x + -8x = -17x -7 + 6x = -6 + -17x Solving -7 + 6x = -6 + -17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '17x' to each side of the equation. -7 + 6x + 17x = -6 + -17x + 17x Combine like terms: 6x + 17x = 23x -7 + 23x = -6 + -17x + 17x Combine like terms: -17x + 17x = 0 -7 + 23x = -6 + 0 -7 + 23x = -6 Add '7' to each side of the equation. -7 + 7 + 23x = -6 + 7 Combine like terms: -7 + 7 = 0 0 + 23x = -6 + 7 23x = -6 + 7 Combine like terms: -6 + 7 = 1 23x = 1 Divide each side by '23'. x = 0.04347826087 Simplifying x = 0.04347826087
| -6m-5=-17 | | 5-3(w+4)=-10(r-3) | | 7x-5-x=-1-6x+6-3x | | -9d-4+3d=27 | | 59-9x=149 | | -3x^2+7x-6=0 | | m=r-w | | 1+3(r-1)=-2-3r | | c=800-50x+0.25x^2 | | 1.5x+14=42 | | 2x+1+X-1=5 | | (3x+2)10=140 | | 9a-3(2a-x)=20 | | 8z+9-5z=81-5z | | 24=-2x+10x+8 | | 14+6-8=18 | | 3x-5+2x-4=26-2x | | .5(48+24b)=2(17-4b) | | 14x-4x=9x | | 0=-16t^2+70t+9 | | C(v)=0.004v^2-0.62v+30 | | 4v-9=6x+-13 | | 26=-3x+9x | | 5x(2x-8)-2=5(x-3)+3 | | 14.5=5.5h-2 | | w+6=-18 | | (4m-4m)= | | -15d-21=564 | | 5x+15=5x-15 | | 4(m-a)=6 | | 3-2x=5x+9 | | 5.50r+6p=51 |